A Study of Indonesian Students' Interest in Traditional Culture Diversity as Preservation of the Quality of Traditional Martial Arts - Y Hapsari, Ayuningtyas (International Journal of Psychosocial Rehabilitation, 2020)
This study examines the diverse Indonesian traditional arts. Traditional dance, traditional musical instruments, traditional martial arts, and many more are almost extinct traditional cultures. Silat is considered one of Indonesia's traditional cultural arts, which has not been reduced by the younger generation, especially the millennial generation. The selection of respondents in this study is 100 students’ private universities in Bandung, where they have watched shows from these fighters. This show is a new concept, namely the appeal of pencak silat that has been modified with contemporary movements.In this study, we used descriptive methods and verification methods. Path analysis has been used in this study to see how much influence modern Pencak Silat martial arts and promotion carried out through social media towards student interest in traditional martial arts.